AGRUPAMENTO DE DADOS PARA AJUSTES DE MODELOS HIPSOMÉTRICOS E VOLUMÉTRICOS EM POVOAMENTOS DE Pinus oocarpa E Pinus caribaea VAR. hondurensis - Carielo, Plínio (2018)
In this study, we compared data grouping strategies by different models of identity test to fit height-diameter and volume models to reduce the quantity of fits and equation analysis aming, to reduce processing time, as well as the selection errors without losing precision. For fitting volume models, 300 trees were scaling. The area under study has 248,22 ha with Pinus oocarpa and Pinus caribaea var. hondurensis stands, divided in plots among 10 and 16 years-old. This area was inventoried by fixed area sampling with 57 rectangular plots of 600 m² distributed in a systematic wry. Different strategies for data grouping were compared, checking if only one equation (general model) could represent different sources of variation such as plots, species and age, instead of one equation to each source of variation (complete model). The selected models used in different grouping strategies were selected based on standard error of estimate (Syx%), adjusted coefficients of determination (R² aj.) and graphical residues analysis. The fitied equations to each strategy were submitted to model identity test. It was found that related to plots should not be used a single height-diameter equation (general model) to represent all the plots in an inventory even if it is of the same species and/or age. In relation to volume it was observed for the species Pinus oocarpa and Pinus caribaea var. hondurensis that a single equation can be used to estimate the total volume of two species since at the same age, for different settlement level adjustment options.